STUDI PERTUMBUHAN TANAMAN PADA AREAL PASCA TAMBANG DATARAN TINGGI DI KALIMANTAN SELATAN - Ahmad Maulidan; Yudi Firmanul Arifin; Eny Dwi Pujawati (Universitas Lambung Mangkurat, 2021)
This research purposed to analyze the growth of the plants on post-mining landbased on the different vegetation ages. The observation was conducted on post-mining area of PT. Antang Gunung Meratus (AGM) at South Hulu Sungai Regency, South Kalimantan. The data retrieval included high condition and diameter of the plants also the physical and chemical characteristics of soil on reclamation area which aged 1 year, 5 years, and 7 years. The dominant species which were in the research location was sengon, trembesi, and gmelina. The average of plants high age 1 year were sengon 1,99 m, trembesi 1,01 m, and gmelina 0,94 m. The average diameter 1 year plants were sengon 4,13 cm, trembesi 2,48 cm, and gmelina 2,70 cm. The average of plants high age 5 years were sengon 7,89 m, trembesi 7,94 m, and gmelina 8,04 m. The average of diameter 5 years plants were sengon 30,49 cm, trembesi 25,23 cm and gmelina 21,38 cm. The average of high growth and diameter of 7 years old sengon plants is 13,02 m, and is diameter 30,18 cm.Keywords: Post-mining; Growth; Sengon, Trembesi; Gmelina